Monitoring by busy and overlap directors: an examination of executive remuneration and financial reporting quality - Fernández Méndez, C.; Arrondo García, R.; Pathan, Md Shams Tabrize (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
© 2016 Asociación Española de Contabilidad y Administración de Empresas (AECA). We examine the influence of multiple board directorships and boards’ committee memberships on three board supervisory outcomes: executive remuneration, external auditor opinion, and earnings management. The study uses a panel of 122 non-financial companies listed on the Spanish Stock Exchange over the period 2004–2011. Our results show that firms with busy directors offer low executive remuneration and present a low probability of a qualified audit opinion. Furthermore, the results indicate that firms with overlap directors exhibit a higher probability of receiving a qualified audit opinion. Additionally, we find evidence that the overcommitment effects of busy and overlap directors are more evident for large firms. Overall, our findings suggest that busy (overlap) directors are beneficial (detrimental) to the monitoring capability of the board in the Spanish context.